If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1x * x = 4x + -8 Multiply x * x 10 + -1x2 = 4x + -8 Reorder the terms: 10 + -1x2 = -8 + 4x Solving 10 + -1x2 = -8 + 4x Solving for variable 'x'. Reorder the terms: 10 + 8 + -4x + -1x2 = -8 + 4x + 8 + -4x Combine like terms: 10 + 8 = 18 18 + -4x + -1x2 = -8 + 4x + 8 + -4x Reorder the terms: 18 + -4x + -1x2 = -8 + 8 + 4x + -4x Combine like terms: -8 + 8 = 0 18 + -4x + -1x2 = 0 + 4x + -4x 18 + -4x + -1x2 = 4x + -4x Combine like terms: 4x + -4x = 0 18 + -4x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -18 + 4x + x2 = 0 Move the constant term to the right: Add '18' to each side of the equation. -18 + 4x + 18 + x2 = 0 + 18 Reorder the terms: -18 + 18 + 4x + x2 = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 4x + x2 = 0 + 18 4x + x2 = 0 + 18 Combine like terms: 0 + 18 = 18 4x + x2 = 18 The x term is 4x. Take half its coefficient (2). Square it (4) and add it to both sides. Add '4' to each side of the equation. 4x + 4 + x2 = 18 + 4 Reorder the terms: 4 + 4x + x2 = 18 + 4 Combine like terms: 18 + 4 = 22 4 + 4x + x2 = 22 Factor a perfect square on the left side: (x + 2)(x + 2) = 22 Calculate the square root of the right side: 4.69041576 Break this problem into two subproblems by setting (x + 2) equal to 4.69041576 and -4.69041576.Subproblem 1
x + 2 = 4.69041576 Simplifying x + 2 = 4.69041576 Reorder the terms: 2 + x = 4.69041576 Solving 2 + x = 4.69041576 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 4.69041576 + -2 Combine like terms: 2 + -2 = 0 0 + x = 4.69041576 + -2 x = 4.69041576 + -2 Combine like terms: 4.69041576 + -2 = 2.69041576 x = 2.69041576 Simplifying x = 2.69041576Subproblem 2
x + 2 = -4.69041576 Simplifying x + 2 = -4.69041576 Reorder the terms: 2 + x = -4.69041576 Solving 2 + x = -4.69041576 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = -4.69041576 + -2 Combine like terms: 2 + -2 = 0 0 + x = -4.69041576 + -2 x = -4.69041576 + -2 Combine like terms: -4.69041576 + -2 = -6.69041576 x = -6.69041576 Simplifying x = -6.69041576Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.69041576, -6.69041576}
| -2x+3y=0 | | -2(-2x+6)= | | 8x+15=6x+11 | | 9-8x=69-43x | | 9-8x=69-43 | | 2(5-x)=4 | | 3=8-2d | | 5-4b=13 | | x^3-9x^2+18x-6=0 | | x^3+9x^2+18x-6=0 | | 5=6-2k | | 7x+4=3x-12 | | 8=18-5p | | 15-3t=0 | | 21-4m=5 | | 8n-3=3n+27 | | 137-6x=21x+20 | | 5x+6=-134-6 | | 11m+3n-3m+10n= | | 32=3y+2 | | 3x-1=170 | | 22x=4 | | x^2-4x+y=0 | | 20-k=8 | | 3m+1=21 | | 138-3x=24x+18 | | 15=24-3x | | x^3-10x^2+21x-30=0 | | 3y-10x-22=15x-4y+31 | | 3x+114=9x-12 | | 133-2x=34x+17 | | (3z-4)(6+z)=0 |